Effect of Ionic Surfactants on the Resolution of Amines of Hydrated Stannic Oxide Impregnated Thin Layer Chromatography - Kulshrestha, Shail; Awasthi, Alok; Dabral, S.K. (Asian Journal of Chemistry, 2010)
The effect of ionic surfactants on the behaviour of various amines on hydrated stannic oxide impregnated silica gel thin layer chromatography was observed by employing various developing systems of different nature, with or without surfactant solutions of different concentrations. The behaviour of amines was also observed on unimpregnated thin layer chromatography for comparison purpose. Some of the important binary separations are reported.